Borneo Beauty Company - Johnas, Nabila Huda; Fadilis, Neneyyeni; Mohamad Zul, Nur Syafiqah; Jesbin, Rasyidah; Jailin, Siti Aiwa (2016)
The first product produced was called Borneo Beauty Bedak Sejuk which is an organic skincare product for facial care. This product is made of organic ingredient such as gingko biloba, turmeric, and cinnamon that is well known for its benefits to face and not contained any harmful chemicals. In addition, the main objective of the product produced is to create a product that is safe for our skin which is fully based on organic ingredients with affordable price. The product will be market at Borneo Beauty shop located at Alamesra, Kota Kinabalu and will be sale with the price RM 15.50 for one unit. Various promotion strategy will be used such as promotion through the magazines, newspaper, signboard and organize booth to introduce the product to people. There are several competitors existed in the market that have same based product which is Bedak Sejuk like Bedak Sejuk Petani and Bedak Sejuk Bearbery that have the market share which is 5.89% and 70.55% respectively. The advantage of Borneo Beauty Bedak Sejuk are it has an affordable price and it is made of 100% of organic and herbs ingredients. The contribution of the company would be a total RM65,000.00 with a car from all of the Managers to the fund of this company. In the future, Borneo Beauty Co. will expand the market of the Borneo Beauty Bedak Sejuk to outside of Kota Kinabalu and Malaysia. Besides, Borneo Beauty Co. will produce more products that based on organic ingredients.